Endogenous market structure and the gains from foreign direct investment - Roberto A. De Santis; Frank Stähler (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1999)
This paper discusses the gains from foreign direct investment (FDI) in a two country setting with endogenous markets structures under two alternative locations for the oligopolistic industry. If the oligopolistic industry is located in the domestic country only, we show that market concentration occurs if national and multinational firms coexist. In this case, FDI is welfare improving for the foreign country, but welfare declining for the domestic country. If only multinational firms are competitive, the impact on market structure and the welfare of the domestic country is indeterminate, whereas the welfare of the foreign country improves. By contrast, if the oligopolistic industry is located in both countries, then FDI compared to intraindustry trade leads to mutual welfare gains.
Keywords: F12; F15; 330; Foreign direct investment; Multinational enterprises; Imperfect competition; Welfare; Direktinvestition; Intraindustrieller Handel; Neue Außenhandelstheorie; Marktstruktur; Wohlfahrtseffekt; Oligopol; Multinationales Unternehmen; Theorie